2023
DOI: 10.1136/bmjopen-2022-062377
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes as a risk factor for the onset of frozen shoulder: a systematic review and meta-analysis

Abstract: ObjectiveSummarise longitudinal observational studies to determine whether diabetes (types 1 and 2) is a risk factor for frozen shoulder.DesignSystematic review and meta-analysis.Data sourcesMEDLINE, Embase, AMED, PsycINFO, Web of Science Core Collection, CINAHL, Epistemonikos, Trip, PEDro, OpenGrey and The Grey Literature Report were searched on January 2019 and updated in June 2021. Reference screening and emailing professional contacts were also used.Eligibility criteriaLongitudinal observational studies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
(147 reference statements)
0
6
1
Order By: Relevance
“…This mechanism could cause the development of LJM. [18][19][20][21] In this study, LJM was positive in 24% of DM patients (Table 1), higher than the results reported by Clarke et al 22 (7%) and Traisman et al 23 (8.4%). However, this percentage is lower than Arkkila et al 24 This study showed a significant association between LJM and the long duration of DM, as shown in Table 2.…”
Section: Discussioncontrasting
confidence: 60%
“…This mechanism could cause the development of LJM. [18][19][20][21] In this study, LJM was positive in 24% of DM patients (Table 1), higher than the results reported by Clarke et al 22 (7%) and Traisman et al 23 (8.4%). However, this percentage is lower than Arkkila et al 24 This study showed a significant association between LJM and the long duration of DM, as shown in Table 2.…”
Section: Discussioncontrasting
confidence: 60%
“…Diabetes refers to a group of chronic diseases distinguished by hyperglycemia ( 143 ). The two prevalent types of diabetes are T1D and type 2 diabetes ( 143 ).…”
Section: Probdnf and Its Receptors In T1dmentioning
confidence: 99%
“…Diabetes refers to a group of chronic diseases distinguished by hyperglycemia ( 143 ). The two prevalent types of diabetes are T1D and type 2 diabetes ( 143 ). The International Diabetes Federation estimates that 1 in 10 adults currently suffers from diabetes, corresponding to 537 million people worldwide.…”
Section: Probdnf and Its Receptors In T1dmentioning
confidence: 99%
“…Frozen shoulder is one of the common painful and disabling fibro-proliferative disorders characterized by a gradual onset of pain and limitation of glenohumeral range of motion (ROM) that can restrict activities of daily living without any radiological evidence [ 15 , 16 ]. The odds of developing frozen shoulder for patients with DM was 3.7 times the odds for those without DM [ 17 ] and the overall prevalence of frozen shoulder among diabetics was estimated at around 13.4% (95% CI 10.2–17.2%) [ 18 ]. The impact of living with diabetic frozen shoulder is multifactorial including clinical factors such as severe pain, impaired mobility, and disability [ 19 , 20 ] and psychosocial factors such as anxiety, depression, sleep deprivation, and altered domains of QoL [ 19 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%